2018
DOI: 10.4103/ajns.ajns_95_17
|View full text |Cite
|
Sign up to set email alerts
|

Significant effect of anti-tyrosine kinase inhibitor (Gefitinib) on overall survival of the glioblastoma multiforme patients in the backdrop of mutational status of epidermal growth factor receptor and PTEN Genes

Abstract: Introduction:We aimed to assess the effect of anti-tyrosine kinase inhibitors (TKIs) (gefitinib) in overall survival (OS) of the glioblastoma multiforme (GBM) patients in the backdrop of mutational status of epidermal growth factor receptor (EGFR) and PTEN genes.Materials and Methods:All the patients subjected to resection or biopsies were put on gefitinib, and radiotherapy was delivered as per the hospital protocol. EGFR and PTEN mutational spectrum was performed by single-strand conformation polymorphism fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…We next explored more targeted drug treatments for specific signaling pathways based on somatic mutations identified in parental tumors from a routinely performed clinical sequencing panel ( Figure 6D; Table S1). EGFR tyrosine kinase inhibition did not improve the overall survival of patients with glioblastomas (Rich et al, 2004;Uhm et al, 2011), but showed a survival benefit in patients with mutated EGFR in the absence of downstream PTEN mutation (Arif et al, 2018;Mellinghoff et al, 2005). We hypothesized that the clinical benefit could be mutation-specific.…”
Section: Modeling Targeted Drug Treatments Using Gbosmentioning
confidence: 97%
“…We next explored more targeted drug treatments for specific signaling pathways based on somatic mutations identified in parental tumors from a routinely performed clinical sequencing panel ( Figure 6D; Table S1). EGFR tyrosine kinase inhibition did not improve the overall survival of patients with glioblastomas (Rich et al, 2004;Uhm et al, 2011), but showed a survival benefit in patients with mutated EGFR in the absence of downstream PTEN mutation (Arif et al, 2018;Mellinghoff et al, 2005). We hypothesized that the clinical benefit could be mutation-specific.…”
Section: Modeling Targeted Drug Treatments Using Gbosmentioning
confidence: 97%
“…First-generation reversible small-molecule inhibitors, Erlotinib and Gefitinib, which have been shown to be effective in treating non-small cell lung cancer [ 253 ], have also been extensively researched as therapeutic options for GBM [ 254 ]. In fact, early preclinical studies of Erlotinib and Gefitinib presented promising results when tested against GBM cell lines [ 255 , 256 ], but subsequent clinical studies of these ATP-competitive small molecules as monotherapeutic agents [ 257 ] or in combination therapy [ 258 , 259 ] were disappointing. Of note, Erlotinib is highly effective in inhibiting EGFR with kinase domain mutations that are prevalent in lung cancer [ 260 ] as opposed to its low efficacy in blocking EGFR with extracellular domain mutations that are characteristic of GBM [ 261 , 262 ].…”
Section: Rtk Inhibitors and Antagonists With Anti-gbm Propertiesmentioning
confidence: 99%
“…GBM still remains a challenge because these tumors are resistant to anti-EGFR therapy, always relapse ( Stupp et al, 2009 ) and recurrent tumors are less sensitive to chemotherapy than the primary tumor, developing novel anti-EGFR agents remains urgent ( Campos et al, 2016 ; Eskilsson et al, 2018 ). Almost half of the patients carry EGFR-driven tumor with phosphatase and tensin homolog (PTEN) deletion, which are resistant to EGFR target therapy, implying PTEN deficiency plays an important role in resistance to anti-EGFR therapy ( Mellinghoff et al, 2007 ; Arif et al, 2018 ; Brito et al, 2019 ). Using PTEN-deficient glioblastoma cell line U87MG-EGFRvIII screening and U87MG-PTEN counter-screening, we have previously reported that G5-7 selectively blocked Janus kinase 2 (Jak2), preventing GBM proliferation ( He et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%